Return of postpartum ovarian activity in dairy goats supplemented with different levels of energy - Nascimento,Thiago Vinicius Costa (2014)
This study aimed to evaluate the return of post partum ovarian activity in dairy goats supplemented with different levels of energy during the dry period in the semi-arid region of Pernambuco. Twenty-four animals were allocated into four treatments of six animals each: Control, consisting of goats that had access to pasture and only received 4 kg of fresh palm, and three groups with isoproteic supplementation (20% Crude Protein), ranging in TDN content of 65%, 75% and 85%. The daily milk yield showed a linear growth behavior (P <0.05) since day 35th postpartum, when the animals recovered the weight gain and body condition score after 14 and 21 days postpartum, respectively, with slight weight gain in 75% and 85% treatments. Among the reproductive parameters, uterine involution and return to estrus activity showed a decrease in the number of days associated with the higher energy levels (P <0.05). The emergence of the 1st follicles > 2 mm occurred around 33 days postpartum and the maximum diameter of the pre-ovulatory follicle was 5,41mm. These results were not influenced by treatments (P> 0.05). We concluded that the supplementation with different levels of energy promoted a positive effect, as increased productive parameters and reduced the number of days for the reestablishment of the reproductive parameters postpartum; for instance, uterine involution, return to estrus and consequently return of ovarian activity postpartum.